Estudos de associação entre distúrbios do sono e variáveis de saúde bucal - Pereira, Duziene Denardini (2020)
The objective of of the first article of this thesis was to study the sleep disorders and it associated factors in adults in the city of Maringá, State of Paraná; in addition, the association between sleep disorders (i.e., obstructive sleep apnea, snoring, and mouth breathing) with self-perceived oral diseases (i.e., gingival bleeding and tooth loss). The study population was comprised of 1643 subjects, age range from 20 to 65 years, 65.9% women). Subjects answered the self-report questionnaires: a) Sleep Assessment Questionnaire (SAQ), b) North York Dental Health Survey (NYDHS), and c) the World Health Organization Quality of Life (WHOQOL). Data collection took place between August 2011 and March 2012. There was no statistically significant difference between genders; however, statistically significant difference were found for different ethnic groups and educational level. However, oral health self-perception (p<0.001) and gingival bleeding (p<0.002) was significantly worse between patients with sleep disorders against those without sleep disorders. Tooth loss presented little absolute difference between groups (0.8%), and a non-significant odds ratio (1.1). The sick group presented significantly higher prevalence of pain in the teeth and in the region of the temporomandibular joints during mastication (38.3%; odds ratio 1.8 versus 31.6%; odds ratio = 3.9, respectively). It can be concluded that individuals with self-reported sleep disorders present worse oral health as compared with those without sleep disorders. A systematic review was carried out to composse this thesis, in order to answer the research question: “Is there a relationshio between poor oral health and sleep disorders?”. During electronic search in the databases, 5,470 articles were retrieved, of which, after reading titles ans abstracts and subsequent full Reading, 17 were selected. During analysis, 4 more articles were articles were manually entered, totaling 21 papers to composse the review. Cross-sectional and case-control studies were used as inclusion criteria, and for eligibility, they should only include adult patients (≥18 years). Interest in studies published in the last 10 years in English, Portuguese and Spanish was restricted. After data ectraction, little literature on the subject was observed. Still, the measures used to analyze sleep disorders and periodontitis varied widely between surveys, but despite this, it can be conclued that patients with sleep disorders are at greater risk of developing oral diseases, and vice versa. However, this relationship cannot be interpreted in isolation.